Performance Analysis of FSO under Turbulent Channel Using OSTBC - Abdulameer, Lwaa Faisal; Fadhil, Hala (Al-Nahrain Journal for Engineering Sciences, 2018)
Free Space Optics (FSO) plays a vital role in modern wireless communications due to its advantages over fiber optics and RF techniques where a transmission of huge bandwidth and access to remote places become possible._x000D_The specific aim of this research is to analyze the Bit-Error Rate (BER) for FSO communication system when the signal is sent the over medium of turbulence channel, where the fading channel is described by the Gamma-Gamma model. The signal quality is improved by using Optical Space-Time Block- Code (OSTBC) and then the BER will be reduced. Optical 2×2 Alamouti scheme required 14 dB bit energy to noise ratio (Eb/N0) at 10-5 bit error rate (BER) which gives 3.5 dB gain as compared to no diversity scheme._x000D_The results show that using Multiple-Input-Multiple-Output (MIMO) technique represented by Alamouti scheme gives the improved BER performance as compared with no diversity (Single-Input-Single-Output (SISO)) technique.